2022
DOI: 10.36348/sjet.2022.v07i01.003
|View full text |Cite
|
Sign up to set email alerts
|

Physico-mechanical Properties of Basalt-based Brake Pad as Alternative to Ceramics Brake pad

Abstract: A basalt-based automobile brake pad was developed through optimization of the volume fractions and manufacturing parameters, a mathematical model was developed based on rule of mixture for the optimization of the volume fraction and the solution obtained using excel solver is as follow; basalt 38%, cast iron chips 26%, bronze 12%, glass fibre 12% and phenolic resin 12%. The manufacturing parameters were design using full factorial design of three levels and three factors, twenty-seven runs were obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The availability of materials such as seashells comes into question as compared with other readily available secondary waste such as PKS and CS. The question on the availability of materials also connects to the work of Gai Peter Friday et al [40] who developed different basalt-based brake pads with a compressive strength range of 70-137 MPa. Ige et al [35] developed a brake pad using maize husk and obtained a compressive strength value of 103 MPa which is within the recommended range of compressive strength.…”
Section: Comprehensive Strength Analysis and Young's Modulus Of Elast...mentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of materials such as seashells comes into question as compared with other readily available secondary waste such as PKS and CS. The question on the availability of materials also connects to the work of Gai Peter Friday et al [40] who developed different basalt-based brake pads with a compressive strength range of 70-137 MPa. Ige et al [35] developed a brake pad using maize husk and obtained a compressive strength value of 103 MPa which is within the recommended range of compressive strength.…”
Section: Comprehensive Strength Analysis and Young's Modulus Of Elast...mentioning
confidence: 99%
“…The compressive strength of samples A-D in Tables 6, 7 [40], and Sekunowo et al [92]. The recommended range for brake materials is 70-125 MPa according to Sekunowo et al [92].…”
Section: Comprehensive Strength Analysis and Young's Modulus Of Elast...mentioning
confidence: 99%
“…Consequently, there is a rise in density. 42 Increasing the molding pressure results in a reduction in the thickness, since it leads to a decrease in porosity. 30,[43][44][45] Ertan et al 46 also obtained similar research results.…”
Section: Effect Of Compression Molding Pressure On the Density Of Com...mentioning
confidence: 99%
“…Ali et al [105] reported that natural composites with coconut fibres have better thermal stability at elevated temperature about 300°C. Recently, basalt fibre reinforced composites have been explored as high temperature stable reinforcements [111]. Thus, natural fibres have demonstrated that they can be a promising sustainable friction material for brake pads in the future.…”
Section: Characterisation Of Natural Composite Brake Padsmentioning
confidence: 99%
“…Basalt fibres have demonstrated the desired better brake pad properties. Compared to ceramic brake pads, brake pads loaded with basalt fibres exhibited higher shear strength at the cost of compressive strength [111]. Further, Zhao et al [102] depicted that optimal content of basalt fibres as reinforcement is necessary to obtain desired mechanical properties of composite materials.…”
Section: Characterisation Of Natural Composite Brake Padsmentioning
confidence: 99%